Investigation on the Structural Behavior of Shear Walls with Steel Truss Coupling Beams under Seismic Loading - Zhiheng Deng; Changchun Xu; Qiang Hu; Jian Zeng; Ping Xiang (Advances in Materials Science and Engineering)
Based on existing experimental results, the finite element analyses were carried out on shear wall structures with steel truss coupling beams. This work studied the seismic behaviors and the working mechanism of the steel truss coupling beam at the ultimate state and put forward two parameters: the area ratio of web member to chord and the stiffness ratio of coupling beam to shear wall. The seismic optimum design method of the coupling beam was also proposed. Afterwards, a comparative analysis was implemented on the three-dimensional shear wall model with steel truss coupling beams designed by the proposed design method. The results show that the structures designed by the proposed method have excellent seismic behaviors, the steel truss coupling beams have enough stiffness to connect shear walls effectively, and its web members have appropriate cross sections to dissipate seismic energy.